2018
DOI: 10.1016/j.dib.2018.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Data on solubilization, identification, and thermal stability of human Presenilin-2

Abstract: The data presented here are related to the research article entitled “Expression, purification, and preliminary characterization of human presenilin-2" [1].Human Presenilin-2 is the catalytic subunit of γ-secretase and a possible calcium leakage channel (Kimberly et al., 2000; Tu et al., 2006) [2], [3]. HisPS2 which was obtained by overexpression in E. coli strain C43 (DE3) was extracted by detergent solubilisation. The sample isolation efficiency by detergents and the protein identification by mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…All the peptides detected belong to extra-membrane segments (Fig. 2 in Ref [54]), which is similar to the MS result reported for PS1 [62]. The low sequence coverage in MS is probably a result of the inaccessibility of the cleavage sites due to bound detergent.…”
Section: Purification Of Hisps2 From Membrane Fraction By Ni-nta and Secsupporting
confidence: 86%
See 4 more Smart Citations
“…All the peptides detected belong to extra-membrane segments (Fig. 2 in Ref [54]), which is similar to the MS result reported for PS1 [62]. The low sequence coverage in MS is probably a result of the inaccessibility of the cleavage sites due to bound detergent.…”
Section: Purification Of Hisps2 From Membrane Fraction By Ni-nta and Secsupporting
confidence: 86%
“…The detergents used in the study are indicated in Table 1 in Ref. [54]. After solubilization, the supernatant and pellet were separated by centrifugation at 100,000g for 1 h and analyzed by western blot.…”
Section: Solubilization Screeningmentioning
confidence: 99%
See 3 more Smart Citations